Population and Human and Social Development Part-III - Planning Commission (Planning Commission, 2000)
Goa with relatively high income, literacy and good health care infrastructure was the first UT to achieve the replacement level of fertility [Total Fertility Rate (TFR) of 2.1] Kerala, the first State to achieve replacement level of fertility in 1988 did so in spite of relatively low per capita income (PCI) proving that in the Indian context economic development is not an essential pre-requisite for achieving small family norm Tamil Nadu which was the second state to achieve replacement level of fertility, did so in spite of low PCI, higher Infant Mortality Rate (IMR) and lower female literacy rate than Kerala.
Planning Commission (Health, Nutrition and Family Welfare Division), Government of India